2006
DOI: 10.1055/s-2006-949523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orally Administered Phenylalanine with and without Glucose on Insulin, Glucagon and Glucose Concentrations

Abstract: In summary, phenylalanine in an amount moderately greater than that in a large protein meal stimulates an increase in insulin and glucagon concentration. It markedly attenuates the glucose-induced rise in plasma glucose when ingested with glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…We found positive correlations between blood glucose levels and body weight, and between glucose levels and visceral fat deposition. Previous studies have indicated that glucose homeostasis in adulthood is programmed during gestation [78-80] at a time when the hypothalamus is vulnerable to excitotoxic injury [1-6]; and several prospective studies have found associations between early life adiposity and weight gain with the development of diabetes in later life [81]. Our study concluded when the animals reached 5 months of age (mature adulthood).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We found positive correlations between blood glucose levels and body weight, and between glucose levels and visceral fat deposition. Previous studies have indicated that glucose homeostasis in adulthood is programmed during gestation [78-80] at a time when the hypothalamus is vulnerable to excitotoxic injury [1-6]; and several prospective studies have found associations between early life adiposity and weight gain with the development of diabetes in later life [81]. Our study concluded when the animals reached 5 months of age (mature adulthood).…”
Section: Discussionmentioning
confidence: 57%
“…mAChRs are acetylcholine receptors highly expressed in the hypothalamus [4], and injections of muscarine into the 3 rd cerebral ventricle causes an increase in hepatic venous plasma glucose levels in rats [5]. Previous studies have linked phenylalanine consumption with elevated serum insulin and glucagon levels in healthy subjects [6], and artificial sweetener consumption has been associated with a paradoxical increase in body weight in several [7-9], but not all [10] epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…That Phe deficiency downregulated TOR expression may be due to the effect of Phe on insulin production. In humans, Phe deficiency reduced serum insulin concentrations [63]. It was reported that low insulin concentrations decreased TOR expression in the muscle cells of rainbow trout (Oncorhynchus mykiss) [64].…”
Section: Phe Regulated Nf-kb P65 I-kba and Tor Gene Expressions In Tmentioning
confidence: 99%
“…Healthy nondiabetic volunteers are being studied first. To date, insulin and glucose responses to ingestion of glycine (3), proline (4), arginine (5), phenylalanine (6), isoleucine (7), and leucine (8) individually have been reported. In this article, we describe the response to lysine ingestion.…”
Section: Introductionmentioning
confidence: 99%